Cathodal transcranial direct current stimulation of the posterior parietal cortex reduces steady-state postural stability during the effect of light touch. Issue 14 (28th September 2016) - Ishigaki, Tomoya; Imai, Ryota; Morioka, Shu
Abstract : Touching a stable object with a fingertip using slight force (<1 N) stabilizes standing posture independent of mechanical support, which is referred to as the effect of light touch (LT). In the neural mechanism of the effect of LT, the specific contribution of the cortical brain activity toward the effect of LT remains undefined, particularly the contribution toward steady-state postural sway. The aim of the present study was to investigate the cortical region responsible for the reduction of postural sway in response to the effect of LT. Active LT was applied with the right fingertip and transcranial direct current stimulation (sham or cathodal) was applied to the left primary sensorimotor cortex or the left posterior parietal cortex in the two groups. The experiments were conducted using a single-blind sham-controlled crossover design. Steady-state postural sway was compared with the factors of transcranial direct current stimulation (sham or cathodal) and time (pre or post). In the results, the effect of LT reduced postural stability in the mediolateral direction after cathodal transcranial direct current stimulation of the left posterior parietal cortex. No effect was observed after stimulation of the left primary sensorimotor cortex. This indicates that the left posterior parietal cortex is partly responsible for the effect of LT when touching a fixed point with the right fingertip during suprapostural tasks, where posture is adjusted according to the precision requirements. Cortical processing of sensory integration for voluntary postural orientation in response to touch occurs in the posterior parietal cortex.